Improving the Effectiveness of the Learning Process Through a Socio-Emotional Approach in Managing Grade 3 Students at Surgi Mufti 5 Model Elementary School - Diani Ayu Pratiwi; Adi Syahputra; Alfi Nasthi Fauziah; Khalishah Nurul Salamah; Rahma Aulia (COMPETITIVE: Journal of Education, 2024)
The professional quality of educators can be demonstrated in the ability to manage classes and teach effectively in the sense that educators are able to provide learning to students to master learning materials that are directed in accordance with curriculum objectives. In managing a class, an educator should be able to control or control student behavior, so that they are directly involved in the learning process. Given this, in this study the researcher tried to put forward a socio-emotional approach in helping teachers manage classes in schools, especially in elementary schools. When conducting this type of qualitative research, the case study method will be used by the researcher. The research was conducted using two data sources, namely primary data and secondary data. The data analysis method used to analyze this research is an interactive analysis mode.